WAYS TO REDUCE RISKS AFFECTING THE INCREASE OF ENTERPRISE INCOME - Sadullayev Oybek Turdiali ugli (American Journals, 2024)
In this article, the types of risks affecting the income of enterprises, the factors of their occurrence and different approaches to prevention are proposed. In addition, the concept of “revenue-factors-risk-revenue” impact has been developed to minimize the risks affecting the income of enterprises.
Keywords: Enterprise income, risk, types of risk, financial risk, market risk, liquidity risk, differential marketing strategy, SMART methodology, BIA method, “income-factors-risk-income” concept.